Análise do sistema de coleta simultânea do perfil vertical de CO2 no Pantanal mato-grossense - Oliveira, Lúcio Gonçalves Barbosa de (2018)
Changes in atmospheric levels of carbon dioxide in the last 200 years can affect the biomes of wetlands, generating climate uncertainties. However, studies that contribute to the understanding of the global carbon balance need to be improved. Then, using only the covariance system of turbulent vortices in these studies can lead to misinterpretations of biological activities of the forest ecosystem. This work aims to improve the instrument simultaneously collecting the vertical profile of CO2 as well as to calculate the S component of the net CO2 exchange of the ecosystem. The most important change was the exchange of the datalogger system, as well as the separation of the electronic components from the electromechanical ones. The dataset used covers the years 2016 and 2017. The canopy stock was calculated considering the below point at 1.05 m and the highest at 18.30 m. The new CO2 profiling instrument resulted in a modular system and its components did not need to be welded together. The highest values of CO2 concentration were obtained for the months in which the precipitations started. The vertical profile of CO2 presents higher concentration of CO2 at night with maximum values close to the surface. In general, the CO2 storage in the canopy (S) shows a negative peak during the first hours of the morning decreasing until the end of the afternoon. The change and updates in the instrument of analysis of vertical profile of CO2 besides reducing the cost of the instrument increased the efficiency of the produced data. And the CO2 storage in the canopy corroborates studies in wetlands.